INTERPERSONAL VIOLENCE IN A TRADITIONAL SOCIETY. FORMS OF AGGRESSION AND SOCIAL CONTROL IN CHILE. XIX CENTURY - Salinas Meza, René (Revista de Historia Social y de las Mentalidades, 2011)
this article examines the interpersonal  violence like a daily facet of the  chilean  society of 19th century.  in this century, the  violence was not a penalized conduct and  was a cross-sectional idea to all the groups  and social spaces and were expressed from  the domestic violence to rural banditry  characteristic of 19th century, being used  like as a mean of resolution of conflicts or  strategy to survival and to like a reinfor - cing of the masculinity.  in addition, the  violence was legitimized by the courts,  who emphasized the necessity to punish  conducts considered transgressions, before  to distribute justice.  the violence also was  facilitated by the bad conditions of life of  the  chilean villages of 19th century and  thigh social confliction, exceeding the  effectiveness of the state codes of control of  the violence through its judicial organisms.
Keywords: interpersonal violence; social confliction; sociability spaces; violent conducts